Response to Bodin and Grote regarding postdoctoral recruitment in clinical neuropsychology. Issue 5 (3rd July 2016) - Nelson, Aaron; Bilder, Robert M.; O'Connor, Margaret; Brandt, Jason; Weintraub, Sandra; Bauer, Russell M.
Abstract: Bodin and Grote convey their opinion that the field of clinical neuropsychology would be best served by a match system for recruitment into postdoctoral training. We critically review their arguments and offer an alternative point of view. Our view considers the current state of the match system in neuropsychology, incorporates comparisons with other disciplines that rely on a match system, and addresses the role of postdoctoral training and the specialization that takes shape at this level. We make recommendations aimed at promoting greater unity among postdoctoral training programs with the goal of focusing leadership efforts on advancing our shared mission of providing the highest quality training in clinical neuropsychology.